Persepsi Kreditur dan PPAT Terhadap Kualitas Layanan Hak Tanggungan Terintegrasi Secara Elektronik - I Made Dwi Gunarta; Akur Nurasa; Sukmo Pinuji (Tunas Agraria, 2020)
The success of the Badung Regency Land Office in issuing HT-el Certificate, the first in Indonesia cannot be separated from the support of the Creditors and PPAT as the main users of HT-el Services. This innovation is an effort to realize the digitalization of services and overcome various existing weaknesses. Creditors and PPAT as the main users are important instruments in providing an overview of HT-el service quality, because basically the success of an organization in providing a service depends on how well the perception of service users will reflect the level of user satisfaction and the profitability of the organization. HT-el Service User Perception (Creditor and PPAT) assessed using the e- Govqual Method illustrates that the Quality of HT-el Services at the Badung District Land Office is very good, this is evidenced by positive responses to the Efficiency, Trust and Realibility as well as Citizen Support. This is an effort to create excellent service in the land sector based on the principles of efficiency and effectiveness in implementing activities.